Biodiversity and integration of ecological characteristics of species in spatial pattern analysis - Z. Mohebi; H. Mirzaei (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Assessment of biodiversity is a key factor in understanding of function and ecosystem management. Nevertheless, an operating procedure for assessing biodiversity and spatial pattern has not been established yet. Therefore, this empirical study was conducted to explore the role of diversity of species in the spatial patterning of tow shrub herbaceous communities.  METHODS: First, the biodiversity analysis was performed by Past3 software to compare the relationship between the two communities. Secondly, the distance and quadrat indices were employed to explore the spatial relationship of dominant species with diversity. In this regard, 64 and 84 plant species recorded in two vegetation types were investigated. Distribution patterns were extracted by distance and quadrat indices and Ecological Methodology software. FINDINGS: The results showed that vegetation type 2 had more diversity and richness compared to vegetation type 1. Besides, the spatial distributions of dominant species (Astragalus gossipinus and Bromus tomentellus) in the two vegetation types were clumped and random with tendency to be clumped. The Scrophulariaceae, Malvaceae, Papaveraceae, and Euphorbiaceae families were not found in vegetation Type 1, and vegetation Type 2 had no species of the Boraginaceae, Rosaceae, Thumeliaceae, Capparidaceae, Oleaceae, Sistaceae, and Dispaceae families. The results showed significant differences in the number of Gaminae and Legominosea families between the two vegetation types.  CONCLUSION: It was concluded that in communities with a dominant cover of shrub, the distribution pattern was clumped, and quadrat indices were less efficient than distance indices. While, in high-diversity communities with a predominant cover of gross, spatial distribution was random and distance and quadrat indices were more convergent. ==========================================================================================COPYRIGHTS©2021 The author(s). This is an open access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original authors and source are cited. No permission is required from the authors or the publishers. ==========================================================================================